2013
DOI: 10.4028/www.scientific.net/amr.838-841.2477
|View full text |Cite
|
Sign up to set email alerts
|

The Public Participation in Environmental Protection and the Sustainable Development

Abstract: There is more and more environmental crisis in our beautiful earth and in our country. According to history, human can draw a correct conclusion and selection that is choosing sustainable development way to improve the harmony between human and natural world. This dissertation finds that the public to participate in Environmental Protection to solve the environment problem is capital. The author try to build a model of investment to environmental protect and carry on imitation calculation on the practical case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…To a certain extent, investments in environmental protection can improve China's environmental quality (Quah & Boon, 2003;Xue et al, 2014;Zhang, 2014), but under the incentive of competition, local governments reduce the scale of these investments.…”
Section: Mechanism Analysis Of the Constraints Created By Economic Gr...mentioning
confidence: 99%
See 1 more Smart Citation
“…To a certain extent, investments in environmental protection can improve China's environmental quality (Quah & Boon, 2003;Xue et al, 2014;Zhang, 2014), but under the incentive of competition, local governments reduce the scale of these investments.…”
Section: Mechanism Analysis Of the Constraints Created By Economic Gr...mentioning
confidence: 99%
“…To a certain extent, investments in environmental protection can improve China's environmental quality (Quah & Boon, 2003; Xue et al, 2014; Zhang, 2014), but under the incentive of competition, local governments reduce the scale of these investments. These investments are often large in scale, long in cycle, and slow in return; they cannot deliver political achievements during the 5‐ to 10‐year tenure of officials in the jurisdiction.…”
Section: Mechanism Analysis Of the Constraints Created By Economic Gr...mentioning
confidence: 99%
“…For example, some studies concluded that the total emission intensity of investment in environmental governance had a significant negative impact [ 8 , 9 ], that is, the greater the investment in governance, the stronger the emission. However, other scholars believe that investment in environmental governance has a positive effect on environmental pollution [ 10 , 11 ].For example, by using provincial panel data from 2003 to 2012, Gao (2015) concluded that environmental investment had a positive role in promoting industrial emission reduction in central and western China [ 12 ]. Some scholars also believe that the positive effect of environmental governance investment on environmental pollution is affected by factors such as governance structure and technology level [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%